Caffeine, Coffee, Tea and Risk of Rheumatoid Arthritis: Systematic Review and Dose-Response Meta-analysis of Prospective Cohort Studies - Asoudeh, Farzaneh; Dashti, Fatemeh; Jayedi, Ahmad; Hemmati, Amirhossein; Fadel, Abdulmannan; Mohammadi, Hamed (Frontiers in Nutrition, 2022)
Objective: Prospective cohort studies on coffee, tea and caffeine in relation to the risk of rheumatoid arthritis (RA) have shown conflicting results. The aim of this study was to conduct a dose–response meta-analysis of cohort studies on the association between dietary caffeine, different types of coffee and tea consumption and the risk of RA. Methods: PubMed/Medline, Scopus and EMBASE were searched up to July 2021 to identify relevant studies that had considered different types of coffee (caffeinated or decaffeinated), tea or caffeine exposure with RA as the main, or one of the, outcome(s). Two authors independently screened 742 publications. Finally, 5 prospective cohort studies were included in our meta-analysis. Pooled relative risks (RRs) were calculated by using a fixed-effects model. We also performed linear and non-linear dose-response analyses to examine the dose-response relations. Results: Comparing extreme categories, we found a positive, significant association between coffee (RR: 1.30; 95% CI: 1.04-1.62; I2 = 0%, n = 5) and decaffeinated coffee (RR: 1.89; 95% CI: 1.35-2.65; I2 =38.1%, n =3) consumption and risk of RA. One additional cup of coffee consumed per day was associated with an increased risk of RA by 6% (95% CI: 1.02-1.10; I2 = 0%;). This increase in the risk of RA for one cup/d of decaffeinated coffee was 11% 95% CI: 1.05-1.18; I2 = 38). No significant association was observed between caffeinated coffee, tea or caffeine intake and the risk of RA. Conclusion: We found that a higher intake of coffee and decaffeinated coffee was associated with increased risk of RA. No significant association between caffeinated coffee, tea or caffeine intake and the risk of RA was observed